2018
DOI: 10.1136/bmjopen-2017-020634
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of congenital anomalies of the kidney and urinary tract: cross-sectional results of a community-based screening and referral study in China

Abstract: ObjectiveTo establish an effective screening model of congenital anomalies of the kidney and urinary tract (CAKUT) using ultrasound among neonates in Shanghai, China.DesignCross-sectional study.SettingA three-level screening model for CAKUT in neonates based on the child healthcare system was established since 2010 in Minhang District, Shanghai, China.ParticipantsDuring 2010–2015, neonates with criteria such as preterm, low birth weight and so on were eligible to participate in the study. Cases with renal pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, prenatal ultrasonographic diagnosis may fail to detect these congenital anomalies in oligoamnios and other rare situations ( 4 ). Lots of attempts have been made for CAKUT screening during the early postnatal period ( 5 8 ). The current study presents such screening in 1-month-old infants and follow-up in 6 months conducted in the medical centers in Zhongshan City, China.…”
Section: Introductionmentioning
confidence: 99%
“…However, prenatal ultrasonographic diagnosis may fail to detect these congenital anomalies in oligoamnios and other rare situations ( 4 ). Lots of attempts have been made for CAKUT screening during the early postnatal period ( 5 8 ). The current study presents such screening in 1-month-old infants and follow-up in 6 months conducted in the medical centers in Zhongshan City, China.…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by bilateral cystic kidney in 50/587 cases. In a Chinese study, urinary ultrasound screening was performed in 8827 infants 22 . Eleven cases of hydronephrosis, seven cases of unilateral renal aplasia, two cases of renal duplication, two cases of renal dysplasia, one case of multicystic dysplastic kidney, one case of renal ectopia, one case of ureterectasia, and one case of renal cyst were observed.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study of congenital malformations showed that 73% of cases of congenital hydronephrosis were diagnosed prenatally [ 8 ]. In countries where prenatal ultrasound examination is rare, postnatal ultrasound in children with UTI, or those at higher risk, could also detect congenital abnormalities [ 36 , 37 ]. According to other publications, the incidence of prenatally diagnosed megaureter is not currently known and may be due to the fact that detection of a dilated ureter by ultrasound prenatally is a difficult endeavor [ 8 ].…”
Section: Discussionmentioning
confidence: 99%